Development of a Multiplex Loop-Mediated Isothermal Amplification (LAMP) Method for Simultaneous Detection of Spotted Fever Group Rickettsiae and Malaria Parasites by Dipstick DNA Chromatography - Lavel Chinyama Moonga; Kyoko Hayashida; Naoko Kawai; Ryo Nakao; Chihiro Sugimoto; Boniface Namangala; Junya Yamagishi (Diagnostics, 2020)
Spotted fever group (SFG) rickettsiae causes febrile illness in humans worldwide. Since SFG rickettsiosis’s clinical presentation is nonspecific, it is frequently misdiagnosed as other febrile diseases, especially malaria, and complicates proper treatment. Aiming at rapid, simple, and simultaneous detection of SFG Rickettsia spp. and Plasmodium spp., we developed a novel multiple pathogen detection system by combining a loop-mediated isothermal amplification (LAMP) method and dipstick DNA chromatography technology. Two primer sets detecting SFG Rickettsia spp. and Plasmodium spp. were mixed, and amplified products were visualized by hybridizing to dipstick DNA chromatography. The multiplex LAMP with dipstick DNA chromatography distinguished amplified Rickettsia and Plasmodium targeted genes simultaneously. The determined sensitivity using synthetic nucleotides was 1000 copies per reaction for mixed Rickettsia and Plasmodium genes. When genomic DNA from in vitro cultured organisms was used, the sensitivity was 100 and 10 genome equivalents per reaction for Rickettsia monacensis and Plasmodium falciparum, respectively. Although further improvement will be required for more sensitive detection, our developed simultaneous diagnosis technique will contribute to the differential diagnosis of undifferentiated febrile illness caused by either SFG Rickettsia spp. or Plasmodium spp. in resource-limited endemic areas. Importantly, this scheme is potentially versatile for the simultaneous detection of diverse infectious diseases.